2016
DOI: 10.1007/s11121-016-0723-7
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the Effectiveness of Interactive Middle School Cannabis Prevention Programs

Abstract: This meta-analysis examines the effectiveness of interactive middle school-based drug prevention programs on adolescent cannabis use in North America, as well as program characteristics that could moderate these effects. Interactive programs, compared to more didactic, lecture style programs, involve participants in skill-building activities and focus on interaction among participants. A systematic literature search was conducted for English-language studies from January 1998 to March 2014. Studies included ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 54 publications
0
27
0
3
Order By: Relevance
“…Most commonly, programs have been developed and evaluated in school, family, and community settings. Evidence is mixed amid heterogeneity of methodology and outcomes between studies, but there is some support for parenting-focused (Allen et al, 2016), school-based teacher-led (Lize et al, 2017), and peer-led prevention programs (MacArthur, Harrison, Caldwell, Hickman, & Campbell, 2016).…”
Section: Preventionmentioning
confidence: 99%
“…Most commonly, programs have been developed and evaluated in school, family, and community settings. Evidence is mixed amid heterogeneity of methodology and outcomes between studies, but there is some support for parenting-focused (Allen et al, 2016), school-based teacher-led (Lize et al, 2017), and peer-led prevention programs (MacArthur, Harrison, Caldwell, Hickman, & Campbell, 2016).…”
Section: Preventionmentioning
confidence: 99%
“…5 To help facilitate the increase in cannabis education, it will be important to focus on the strategic approach in delivery and the specific content to be addressed. Systematic reviews [8][9][10] have concluded that approaches to delivering cannabis content are more effective in reaching adolescents and limiting use when: digital-based (e.g., social media); facilitated by a non-teacher; frequent and factual; and peer and family member-engaging. Furthermore, applying scare tactics, the "just say no" approach, and over-assertions of cannabis' harms (e.g., emphasizing causation over risk) are cautioned against.…”
Section: Resultsmentioning
confidence: 99%
“…The literature has indicated many of the programs that are effective in preventing various risk behaviors in adolescence are delivered by teachers trained prior to the implementation of the intervention program. Studies show programs implemented by the educational staff/teachers are more effective than programs delivered by an external mentor or supervisor who is not part of the school staff (Lize et al, 2017;Gá zquez, 2010;Waschbusch et al, 2018). Intervention programs delivered by school staff as part of the school's curriculumroutine have a longer-term chance of implementation and preservation.…”
Section: International Journal Of Educationmentioning
confidence: 99%